1140 Sleep Disturbances, Lifestyle, And Self-Management In Adults With Subarachnoid Hemorrhage. (27th May 2020) - Byun, E; McCurry, S; Kwon, S; Kim, B; Thompson, H
Abstract: Introduction: Subarachnoid hemorrhage (SAH) survivors often suffer sleep disturbances. Self-management strategies focusing on lifestyle changes and health-promoting behaviors may improve sleep in SAH survivors. Few studies have examined sleep in SAH survivors, and little is known about sleep management practices used to improve their sleep. The purposes of this study were to: 1) describe the prevalence of sleep disturbances using subjective and objective sleep measures, and 2) explore interest in and engagement with self-management practices to promote sleep health in SAH survivors. Methods: We conducted a cross-sectional study with a convenience sample of 30 SAH survivors recruited from a university hospital. We assessed sleep quality using the Pittsburgh Sleep Quality Index (PSQI), daytime sleepiness using the Epworth Sleepiness Scale (ESS), and objective sleep using wrist actigraphy. We conducted content analysis of semi-structured interviews, with two authors each coding sleep disturbances and self-management practices addressing sleep. Results: Seventy-three percent of SAH survivors reported poor sleep quality (PSQI > 5) and 27% had daytime sleepiness (ESS > 10). Actigraphy analysis indicated that 41% of SAH survivors slept less than 7 hours or more than 9 hours. Interview content analyses suggested 3 themes and 15 sub-categories: 1) Sleep disturbances (difficulties in falling asleep, wake after sleep onset, daytime sleepiness, too much or insufficient sleep, and poor sleep quality), 2) Sleep management practices (exercise, regular sleep schedule, relaxation, keeping busy and staying active, changing beverage intake, taking supplements, taking medication, recharging energy, and barriers to sleep management), and 3) Healthcare providers (discussing sleep problems with health care providers). Conclusion: Sleep disturbances are highly prevalent and an urgent need exists to focus on improving sleep in SAH survivors. Developing tailored interventions that incorporate self-management and lifestyle change would be a critical next step to improve sleep and promote health in this at-risk population. Support: This research was supported by grants from the National Institutes of Health/National Institute of Nursing Research (K23 NR017404), University of Washington Institute of Translational Health Science Translational Research Scholars Program (UL1 TR000423), and University of Washington School of Nursing Research and Intramural Funding Program.